(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
Through the analysis of the conflicts between the government of the argentine province of Tucumán and the indigenous communities in the Tafí Valley in the context of the COVID-19 pandemic, we expose the urgent need to legislate with greater clarity the scope of indigenous community ownership rights. The administration of the urgency and the sanitary emergency that suspend internationally recognized rights of the community members, put in evidence the unfinished debates between States and Communities on the management of the territory and the proposals of interculturality in the solutions. These incomplete discussions lead us to the proposal to move from a legal debate to a political one for the autonomy of the native peoples of the American continent.